Great minds of the western intellectual tradition. the crisis of modernity. - Staloff, Darren 1961-; Shearmur, Jeremy 1948-; Kellner, Douglas 1943-; Markos, Louis; Cary, Phillip 1958- (The great courses., 2000)
Lectures based on the seminar course at Columbia University on Western intellectual history augmented by additional lectures by selected "guest" lecturers. Gives a guided tour through 3,000 years of Western thought.